Chemical Modified Carbon Paste Electrode for Potentiometric Determination of Mo(VI) and its Application in Food Analysis and Agriculture Fertilizers. Issue 5 (14th January 2022) - EL‐Sanafery, Safa S.; Abbas, Ashraf A.; Mohamed, Gehad G.
Abstract: Since to the best of our knowledge, there is no potentiometric sensors based on carbon paste electrodes were proposed for the potentiometric determination of molybdenum(VI) ion. In this study, 2, 2′‐(propane‐1, 3‐diylbis(oxy))dibenzoic acid (PBODBA) was synthesized and used as modifier in the fabrication of carbon paste electrode (CPE) for the quantification of molybdenum(VI). The developed electrodes I and II showed hexavalent Nernstian response of 9.80±0.05 and 9.90±0.08 mV decade −1 over the concentration ranges of 1.0×10 −7 –1.0×10 −3 and 1.0×10 −8 –1.0×10 −3  mol L −1, respectively. The electrodes showed good selectivity for Mo(VI). The modified electrodes were applied for the determination of Mo(VI) concentration in masscuaje agricultural fertilizer and spiked juice extractions containing several metals. Abstract :